2011
DOI: 10.1021/es201070t
|View full text |Cite
|
Sign up to set email alerts
|

Performance of School Bus Retrofit Systems: Ultrafine Particles and Other Vehicular Pollutants

Abstract: This study evaluated the performance of retrofit systems for diesel-powered school buses, a diesel oxidation catalyst (DOC) muffler and a spiracle crankcase filtration system (CFS), regarding ultrafine particles (UFPs) and other air pollutants from tailpipe emissions and inside bus cabins. Tailpipe emissions and in-cabin air pollutant levels were measured before and after retrofitting when the buses were idling and during actual pick-up/drop off routes. Retrofit systems significantly reduced tailpipe emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Both DOC and CCVs showed significant reductions in PM 2.5 and UFPs. This is generally consistent with previous invehicle studies, which found reductions of 25-60% for PM 2.5 and 5-70% for UFPs (17,25,27,28). Reductions in UFPs, and to a lesser extent PM 2.5 , with ULSD are also consistent with an earlier in-cabin study using ULSD in combination with DPF (17).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both DOC and CCVs showed significant reductions in PM 2.5 and UFPs. This is generally consistent with previous invehicle studies, which found reductions of 25-60% for PM 2.5 and 5-70% for UFPs (17,25,27,28). Reductions in UFPs, and to a lesser extent PM 2.5 , with ULSD are also consistent with an earlier in-cabin study using ULSD in combination with DPF (17).…”
Section: Discussionsupporting
confidence: 91%
“…Clean air technologies such as diesel oxidation catalysts (DOCs) and crankcase ventilation systems (CCVs) are used to reduce tailpipe and engine emissions, respectively. These technologies, which can be adopted on older buses and are commonly installed on newer buses, are estimated to reduce particulate emissions and onboard concentrations by 20 to 50% (23)(24)(25)(26)(27)(28). The USEPA also required that refineries produce ultralow-sulfur diesel (ULSD) starting in 2006 under the Highway Diesel Fuel Sulfur Control Requirements.…”
mentioning
confidence: 99%
“…In both periods, approximately 55 and 45% were in the 5-30 and 262 30-300 nm ranges, respectively. These results are consistent with previous measurements that 263 suggest that a large proportion of PNCs emitted by road vehicles are less than 300 nm in 264 diameter (Kittelson, 1998; Knibbs and de Dear, 2010;Zhang and Zhu, 2011). However, the 265 precise proportions might differ slightly from those measured in car cabins in other studies.…”
supporting
confidence: 88%
“…This is because most of the experimental data were collected under conditions with windows closed (Fitz et al, 2003), and Liu et al (2010) and Solomon et al (2001) reported that the pollution levels were higher when the windows on the bus were closed. The self-pollution from crankcase emissions was not considered in this study because in-use school buses had fewer cracks or leaks in their crankcases than the older ones (Zhang and Zhu, 2011).…”
Section: Methodsmentioning
confidence: 99%